Proteolytic activity and characteristics of skipjack tuna trypsin loaded alginate–chitosan beads as affected by drying methods and trehalose/glycerol. (2nd September 2022) - Patil, Umesh; Nagarajarao, Ravishankar Chandragiri; Balange, Amjad Khansaheb; Zhang, Bin; Benjakul, Soottawat
Summary: Trypsin‐loaded beads were produced using alginate and chitosan ionotropic gelation. Effects of drying methods (air‐drying and freeze‐drying) on characteristics and relative trypsin activity (RTA) of beads were studied. More homogeneous, spherical and smoother surface with larger size of beads and higher RTA were obtained by freeze‐drying method than those of air‐drying. Trehalose and/or glycerol at different concentrations (2.5 and 5%, w/v) were added in encapsulating materials and RTA of beads after freeze‐drying and after simulated gastric digestion (SGD) was monitored. Freeze‐dried trypsin beads with 5% glycerol (FDTB‐G5) showed highest RTA after SGD. Moreover, highest degradation was attained when fish mince and sodium caseinate were hydrolysed with FDTB‐G5 at a level of 100% of proteins tested in in vitro simulated gastrointestinal tract. Therefore, FDTB‐G5 had better physical characteristics, which could withstand acidic condition and retain trypsin activity, thus favouring proteolysis when delivered to intestinal tract. Abstract : Tuna trypsin loaded in alginate–chitosan beads was stabilised using 5% glycerol. Freeze‐drying could lower the loss in trypsin activity in comparison with air‐drying. Freeze‐dried beads could withstand the simulated gastric condition and was released under intestinal condition to hydrolyse the selected proteins.